2010
DOI: 10.4028/www.scientific.net/amr.89-91.763
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Embrittlement of Submicrocrystalline Ultra-Low Carbon Steel Produced by High-Pressure Torsion Straining

Abstract: The tensile property and hydrogen embrittlement (HE) behavior in the submicrocrystalline ultra-low carbon steel produced by HPT straining were investigated. Elongated grains with 300 nm thickness and 600 nm length with high dislocation density were formed by the HPT straining at a rotation-speed of 0.2 rpm under a compression pressure of 5 GPa. The engineering tensile strength of the HPT processed ultra-low carbon steel for > 5 turns was 1.9 GPa, which is similar to the value of maraging high-alloy steels. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…17) After the HPT process, low temperature annealing at 200°C for 1 h was performed to control the dislocation density in the sample while keeping the grain size. 18) The annealed sample was referred to as HPT + A.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…17) After the HPT process, low temperature annealing at 200°C for 1 h was performed to control the dislocation density in the sample while keeping the grain size. 18) The annealed sample was referred to as HPT + A.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…A sample with almost the same grain size as, but lower dislocation density than SPD, was also tried to be made by annealing SPD at 473 K for 3 600 s (SPD + A) as in Ref. 4). Purity of Fe is shown in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…It should be noted that HPT processing can produce ultrafine grains of less than 1 μm by applying a large amount of strain even for pure metals without contaminated by impurities. Mine et al 31) and Todaka et al 32) conducted tensile tests of HPT-processed Fe-0.01 mass% C after hydrogen charging and small punch tests of HPT-processed ultra-low carbon steel in a hydrogen environment, respectively, to investigate hydrogen-induced changes in their mechanical properties. While those results suggested that hydrogen embrittlement more likely occurs in the specimens with smaller grain sizes, the fracture mechanism has not been fully discussed, and thus the effect of grain boundaries on hydrogen embrittlement of iron is not clear yet.…”
Section: Introductionmentioning
confidence: 99%